STUDI LITERATUR PEMANFAATAN MEDIA FLIPBOOK BERBANTUAN PENDEKATAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI IPAS BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Khumaeroh, Siti; Handoyo, Eko; Sumartiningsih, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the utilization of flipbook media assisted by the Problem-Based Learning (PBL) approach in improving elementary school students' learning outcomes in Natural and Social Sciences (IPAS) based on local wisdom. This research uses a literature review method by analyzing various relevant national and international journals. The findings indicate that flipbook media provides interactive, visual, and flexible learning experiences, while the PBL approach enhances students' critical thinking and problem-solving skills. Integration of local wisdom makes learning more contextual and meaningful. Overall, the combination of flipbook media, PBL, and local wisdom significantly contributes to improving students’ learning outcomes, engagement, and conceptual understanding in IPAS subjects at the elementary level.